A standardization approach to compare treatment safety and effectiveness outcomes between clinical trials and real‐world populations in psoriasis. (2nd July 2019) - Yiu, Z.Z.N.; Mason, K.J.; Barker, J.N.W.N.; Hampton, P.J.; McElhone, K.; Smith, C.H.; Warren, R.B.; Griffiths, C.E.M.; Lunt, M.; Burden, A.D.; ,
Summary: Background: Patients recruited in randomized controlled trials (RCTs) for biologic therapies in psoriasis are not fully representative of the real‐world psoriasis population. Objectives: Firstly, to investigate whether patient characteristics are associated with being included in a psoriasis RCT. Secondly, to estimate the differences in the incidence of severe adverse events (SAEs) and the response rate between RCT and real‐world populations of patients on biologic therapies for psoriasis using a standardization method. Methods: Data from the British Association of Dermatologists Biologics and Immunomodulators Register (BADBIR) were appended to individual participant‐level data from two RCTs assessing ustekinumab in patients with psoriasis. Baseline variables were assessed for association of being in an RCT using a multivariable logistic regression model. Propensity score weights were derived to reweigh the registry population so that variables had the distribution of the trial population. We measured the C ‐statistic of the model with trial status as the dependent variable, and the risk differences in the incidence rate of SAEs in the first year and Psoriasis Area and Severity Index (PASI) after 6 months in the BADBIR cohort before and after weighting. Results: In total 6790 registry and 2021 RCT participants were included. The multivariable logistic regression model had a C ‐statistic of 0.82 [95% confidence interval (CI) 0.81–0.83]. The risk differences for the incidence rate of SAEs and the proportion of patients with PASI < 1.5 were 9.27 (95% CI −3.91–22.5) per 1000 person‐years and 0.95 (95% CI −1.98–4.15), respectively. Conclusions: Our results suggest that RCTs of biologic therapies in patients with psoriasis are not fully representative of the real‐world population, but this lack of external validity does not account for the efficacy–effectiveness gap. What's already known about this topic? Patients with psoriasis who would not be eligible for randomized controlled trials (RCTs) investigating biologic therapies have a greater risk of serious adverse events and lower treatment effectiveness than patients who would have been eligible. What does this study add? Baseline patient characteristics were shown to be predictive of whether a patient would have been eligible for enrolment in an RCT for psoriasis biologic therapy. We did not find any efficacy–effectiveness gap between the sample representative of the real‐world population of patients with psoriasis and the sample representative of the RCT population. Factors outside of baseline patient characteristics, such as observer effect and higher adherence in RCTs, may be more influential in any efficacy–effectiveness gap between trial and real‐world populations of patients with psoriasis. Abstract : Respond to this article